2018
DOI: 10.1074/jbc.m117.807859
|View full text |Cite
|
Sign up to set email alerts
|

Naked mole-rat acid-sensing ion channel 3 forms nonfunctional homomers, but functional heteromers

Abstract: Acid-sensing ion channels (ASICs) form both homotrimeric and heterotrimeric ion channels that are activated by extracellular protons and are involved in a wide range of physiological and pathophysiological processes, including pain and anxiety. ASIC proteins can form both homotrimeric and heterotrimeric ion channels. The ASIC3 subunit has been shown to be of particular importance in the peripheral nervous system with pharmacological and genetic manipulations demonstrating a role in pain. Naked mole-rats, despi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…In the peripheral nervous system, subcutaneous injection of acid (pH 3.5), capsaicin or histamine does not cause the nocifensive or pruriceptive behaviours in NMR that such stimuli characteristically induce in mice [11,12]. This acid insensitivity is a function of altered ASIC responses compared to mouse [19] and a variation in NMR NaV1.7, which renders the channel hypersensitive to proton-mediated block and therefore prevents acid-driven action potential initiation from the skin [18]. Such intrinsic differences in the sensitivity of NMR to acid may explain our observation of significantly lower firing rates in response to application of acid to NMR colonic afferents compared mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the peripheral nervous system, subcutaneous injection of acid (pH 3.5), capsaicin or histamine does not cause the nocifensive or pruriceptive behaviours in NMR that such stimuli characteristically induce in mice [11,12]. This acid insensitivity is a function of altered ASIC responses compared to mouse [19] and a variation in NMR NaV1.7, which renders the channel hypersensitive to proton-mediated block and therefore prevents acid-driven action potential initiation from the skin [18]. Such intrinsic differences in the sensitivity of NMR to acid may explain our observation of significantly lower firing rates in response to application of acid to NMR colonic afferents compared mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Recent single-cell RNA-sequencing analysis of colonic sensory neurones shows discrete expression of such acid-sensitive ion channels with differing populations of mouse colonic afferents, suggesting functional specialism [16]. Compared to mice, NMRs display a similar expression profile of ASICs throughout the nervous system [17], and of those analysed, with the exception of ASIC3, NMR acid sensors show similar activation profiles to those of mice [13,18,19]. NMR TRPV1 is also expressed in sensory afferents and shows similar proton sensitivity to mouse TRPV1 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Acid, or more specifically protons, can activate sensory neurons by the modulation or activation of several different classes of ion channels including activation of TRPV1, acidsensing ion channels (ASICs) and proton-sensing G-proteincoupled receptors (GPCR) and inhibition of certain twopore K + channels (Holzer 2009;Pattison et al 2019). Direct electrophysiological studies have shown that naked mole-rat 1 3 DRG neurons display depolarizing currents to proton application, indeed both TRPV1-like and ASIC-like inward currents have been observed (Smith et al 2011;Schuhmacher et al 2018) and expression of different ASIC subunits appears to be roughly equivalent between mouse and naked mole-rat sensory neurons (Schuhmacher and Smith 2016). When examining the proton sensitivity of cloned acid-sensitive proteins, naked mole-rat TRPV1, ASIC1a and ASIC1b have a similar proton sensitivity to their mouse orthologues (Smith et al 2011); however, the ASIC3 subunit is proton insensitive and appears to shift the proton sensitivity when present in heterotrimers, which may alter sensory neuron acid sensitivity to some extent (Schuhmacher et al 2018).…”
Section: Absence Of Acid-induced Pain In Naked Mole-ratsmentioning
confidence: 99%
“…Direct electrophysiological studies have shown that naked mole-rat 1 3 DRG neurons display depolarizing currents to proton application, indeed both TRPV1-like and ASIC-like inward currents have been observed (Smith et al 2011;Schuhmacher et al 2018) and expression of different ASIC subunits appears to be roughly equivalent between mouse and naked mole-rat sensory neurons (Schuhmacher and Smith 2016). When examining the proton sensitivity of cloned acid-sensitive proteins, naked mole-rat TRPV1, ASIC1a and ASIC1b have a similar proton sensitivity to their mouse orthologues (Smith et al 2011); however, the ASIC3 subunit is proton insensitive and appears to shift the proton sensitivity when present in heterotrimers, which may alter sensory neuron acid sensitivity to some extent (Schuhmacher et al 2018). It was thus puzzling that isolated naked mole-rat sensory neurons can be excited by protons, but why did we observe no acid driven action potentials in nociceptors and no pain behavior?…”
Section: Absence Of Acid-induced Pain In Naked Mole-ratsmentioning
confidence: 99%
“…It is striking that NMRs are resistant to many pathological conditions known to involve ASICs. Recordings of ASIC-mediated currents in dorsal root ganglion (DRG) sensory neurons demonstrated an increased frequency and magnitude of ASIC responses in NMR neurons compared to mouse neurons [ 43 ], with APETx2, an inhibitor of ASIC3-containing ASICs, demonstrating a key role for ASIC3, even though nmrASIC3 does not appear to form functional homotrimers [ 50 ]. Previously we mapped out ASIC expression in different NMR brain regions and observed similar expression between mouse and NMR, a key exception being much lower ASIC4 levels throughout the NMR brain [ 51 ], however, no one has yet studied the function of ASICs in NMR brain neurons.…”
Section: Introductionmentioning
confidence: 99%